ODOR SENSOR DIGITAL (OSD) SEBAGAI PENDETEKSI BAU LUKA UNTUK MENGETAHUI GRADE INFEKSI - Setiawan, Wawan; Leksono, Cipto; Firdaus, Doni Fitri; Saryono, Saryono (Program Kreativitas Mahasiswa - Karsa Cipta, 2014)
Odor Sensor Digital (OSD) is a device used to detect the smell of injuries that reflect the level of infection. How it works OSD in detecting the level of infection is to capture odors contained in the wound, then the result is sent to the laptop and will be translated and summarized by the software (Software). The goal is to determine the level of infection as a basis for determining an accurate diagnosis. OSD will provide convenience for all healthcare professionals who manage patients, both patients with burns and wound infections. This tool is more efficient in detecting the level of infection and treatment more quickly and accurately, so that complications can be prevented Keywords: sensor, wound odor, Odor Sensor Digital (OSD)